Heterologous Production of Glycine Betaine Using Synechocystis sp. PCC 6803-Based Chassis Lacking Native Compatible Solutes - Ferreira, Eunice A.; Pacheco, Catarina C.; Rodrigues, João S.; Pinto, Filipe; Lamosa, Pedro; Fuente, David; Urchueguía, Javier; Tamagnini, Paula (Frontiers in Bioengineering and Biotechnology, 2022)
Among compatible solutes, glycine betaine has various applications in the fields of nutrition, pharmaceuticals and cosmetics. Currently, this compound can be extracted from sugar beet plants or obtained by chemical synthesis, resulting in low yields or high carbon footprint, respectively. Hence, in this work we aimed at exploring the production of glycine betaine using the unicellular cyanobacterium Synechocystis sp. PCC 6803 as a photoautotrophic chassis. Synechocystis mutants lacking the native compatible solutes sucrose or/and glucosylglycerol - ∆sps, ∆ggpS and ∆sps∆ggpS - were generated and characterized. Under salt stress conditions, the growth was impaired and accumulation of glycogen decreased by ~50% whereas the production of compatible solutes and extracellular polymeric substances (capsular and released ones) increased with salinity. These mutants were used as chassis for the implementation of a synthetic device based on the metabolic pathway described for the halophilic cyanobacterium Aphanothece halophytica for the production of the compatible solute glycine betaine. Transcription of ORFs comprising the device was shown to be stable and insulated from Synechocystis’ native regulatory network. Production of glycine betaine was achieved in all chassis tested, and was shown to increase with salinity. The introduction of the glycine betaine synthetic device into the ∆ggpS background improved its growth and enabled survival under 5% NaCl, which was not observed in the absence of the device. The maximum glycine betaine production [64.29 µmol/gDW (1.89 µmol/mg protein)] was reached in the ∆ggpS chassis grown under 3% NaCl. Taking into consideration this production under seawater-like salinity, and the identification of main key players involved in the carbon fluxes, this work paves the way for a feasible production of this, or other compatible solutes, using optimized Synechocystis chassis in a pilot-scale.